Exante evaluation of nutrition and health benefits of biofortified cassava roots in nigeria: the dalys approach - Manyong, Victor M.; Bamire, A.; Sanusi, I.; Awotide, D. (2004)
Cassava is a major staple that supplies more than 50% of daily energy to more than 200 million persons in sub-Saharan Africa (SSA). Cassava roots are known to be low in micronutrients such as vitamin A, iron, and zinc. Micronutrient deficiencies threaten the lives of millions of poor households and those located in remote rural areas of SSA often not targeted by fortification programmes. This paper presents results from an ex-ante evaluation of nutrition and health benefits of increased vitamin A status of cassava roots through biofortification for at-risk-target-groups using the disability-adjusted life years (DALYs) approach. Results showed that Vitamin A deficiency (VAD) causes an annual loss of about 553,000 years of healthy life in Nigeria with children constituting more than forty percent. Biofortified cassava would reduce VAD by 4.42%, 11.73%, and 3.14% for children, pregnant women, and lactating women respectively in the pessimistic scenario. Results for the optimistic scenario are 28.79%, 76.39, and 20.45% respectively. The biofortification of cassava roots would result in annual gains of about 33,000 years of healthylife and avert 166 child deaths per year for the pessimistic scenario and about 220,000 years life and 1272 child deaths per year for the optimistic scenario. In economic terms, such a programme would bring gains amounting to about $10 million per year, which Biofortification, DALYs, Economics, Health, corresponds to an internal rate of return (IRR) as high as 92.4% in the pessimistic scenario. Results in the optimistic scenario are about $63 million per year and an IRR of 165.3%. A research and development effort aimed at the biofortification of cassava roots is a powerful strategy in the fight against hidden hunger from micronutrient deficiencies, which African governments at the national and local levels, and international investors should support to improve the standard of living of the people in SSA.